PERBEDAAN TINGKAT PENGETAHUAN PEMELIHARAAN KESEHATAN GIGI DAN MULUT MELALUI PENYULUHAN DENGAN MEDIA POSTER DAN VIDEO PADA SISWA KELAS IV DAN V SDN 2 KALIAKAH, KEC.NEGARA TAHUN 2022 - Ni Nengah Sumerti; Anak Agung Gede Agung; Ni Wayan Arini; Ni Komang Ayu Ria Arnata (Jurnal Kesehatan Gigi (Dental Health Journal), 2022)
Dental and oral health problems in the school age group are an important concern in the development of dental and oral health because children are a group that is vulnerable to dental and oral diseases. Efforts to educate about the maintenance of dental and oral health to target school children are the first priority. The purpose of this study was to determine differences in the level of knowledge of dental and oral health maintenance through outreach with posters and videos media which was carried out online to students of SDN 2 Kaliakah, Negara Subdistrict in 2022. The research was a pre-experimental one group pretest and posttest design. The type of data used is secondary data. The results showed the percentage level of knowledge before counseling with the most poster media with less criteria was 36.67% and increased to very good criteria 86.67%. The most video media with sufficient criteria is 40%, and after counseling all students have very good criteria 100%. The average level of knowledge with poster media is 53 (less), after counseling it becomes 89.17 (very good), while before counseling with video media 59.17 (less) it increases after counseling to 93.83 (very good). The Mann-Whitney analysis test showed a significant difference in the level of knowledge through counseling with video and poster media with a significance value of p 0.05. In conclusion, the level of knowledge of respondents using video media is higher than using posters.